2010
DOI: 10.1099/mic.0.033670-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of an RNA polymerase interacting protein, MsRbpA, from Mycobacterium smegmatis in phenotypic tolerance to rifampicin

Abstract: Rifampicin and its derivatives are at the forefront of the current standard chemotherapeutic regimen for active tuberculosis; they act by inhibiting the transcription activity of prokaryotic RNA polymerase. Rifampicin is believed to interact with the b subunit of RNA polymerase. However, it has been observed that protein-protein interactions with RNA polymerase core enzyme lead to its reduced susceptibility to rifampicin. This mechanism became more diversified with the discovery of RbpA, a novel RNA polymerase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
64
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(71 citation statements)
references
References 23 publications
6
64
1
Order By: Relevance
“…Interactions between RbpA and core RNAP have been proposed previously, and putative interactions have been mapped to two widely spaced regions of RNAP (18,27). However, our RbpA-SID/RPo structural model is completely incompatible with previous claims that RbpA interacts with RNAP either in the active-site channel near the Rif binding site (27,28) (Fig. S6A) or with a different region of the β-subunit (18) (Fig.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Interactions between RbpA and core RNAP have been proposed previously, and putative interactions have been mapped to two widely spaced regions of RNAP (18,27). However, our RbpA-SID/RPo structural model is completely incompatible with previous claims that RbpA interacts with RNAP either in the active-site channel near the Rif binding site (27,28) (Fig. S6A) or with a different region of the β-subunit (18) (Fig.…”
Section: Discussioncontrasting
confidence: 56%
“…S6). The binding site near the Rif pocket was originally inferred based on functional data (28) and then refined on the basis of a single cross-link (27). The other β-subunit determinant was identified using cleavage experiments through hydroxyl-radicals generated from Fe(III) (S)-1-(p-Bromoacetamido-benzyl) ethylene diamine tetraacetic acid (Fe-BABE) attached to the lone Cys residue of the RbpA-RCD.…”
Section: Discussionmentioning
confidence: 99%
“…Though study of the involvement of sigma factors in rifampin tolerance is not exhausted, recent promising research on the origin of rifampin tolerance in M. tuberculosis is being focused on RNAP accessory proteins. Both GroEL1 (19) and RbpA (8) have been suggested to stabilize RNAP and affect the accessibility of rifampin to its binding site, though it remains to be determined if these proteins cause rifampin tolerance at physiological concentrations in an experimental model of infection.…”
Section: Discussionmentioning
confidence: 99%
“…M. tuberculosis must therefore have an alternative mechanism to circumvent rifampin inhibition and allow for continued transcription. Recent studies have revealed that some accessory proteins such as GroEL1 and RbpA can bind RNAP and prevent rifampin inhibition in vitro (8,19). Here, we investigate whether altering the sigma factor usage can have a similar impact on the affinity of rifampin for RNAP, allowing transcription in its presence.…”
mentioning
confidence: 98%
“…An amount of 100 g of total protein was loaded in each case. M. smegmatis RNA polymerase ␣-subunit was used as the internal loading control (15). Antibodies against RNA polymerase ␣-subunit (15), Rel Msm (19), and MS_RHII-RSD were raised in New Zealand White rabbits at the Indian Institute of Science (IISc) in-house Central Animal Facility.…”
Section: Methodsmentioning
confidence: 99%